Avaliação da estabilidade oxidativa do biodiesel (B100) comercial na presença de antioxidantes naturais da casca de romã - Witt, Elaine de Paula (2018)
Biodiesel is a sensible fuel to the oxidation, because it presents in its chemical composition some free radicals. To raise its oxidative stability it is necessary to add synthetic or natural antioxidants. Among the natural antioxidants there is a variety of plants that may be used with the function to avoid or to detain the chain reactions of oxidation, which are capable to promote or inactivate the free radicals interrupting the reaction in the biofuel chain. In the pomegranate peel is possible to detect some phenolic compounds and antioxidants compounds beyond several bioactive compounds with some mechanisms of action that are similar to the vitamin C, vitamin E and beta-carotene. The aim of this study was to evaluate the biodiesel oxidative stability in the presence of some natural oxidants which were extracted from the pomegranate peel by the conventional method of extraction (Soxhlet and the grease and oils extractor – Goldfish) and by the supercritical extraction with CO2 in a condition of constant pressure (200 bar), some variation in the temperature (35, 45 and 55 oC) and in the presence of the cosolvent ethanol (0, 2,5 and 5 mL). The extracts were measured in relation to the antioxidant activity by the DPPH• radical inhibition. The extract obtained by the Soxhlet method with ethyl acetate presented 94,16% of inhibition in the 1000 µg.mL-1 concentration. The phenolic compound content was used with the FolinCiocalteu reagent, which was evaluated for the extracts. The sample obtained by the grease and oils extractor – Goldfish with an ethanol solvent, showed a density of 98,62mg of EAG/g of the extract. The commercial biodiesel was additive with some extract of the pomegranate peel and with the synthetic antioxidants BHA and BHT and submitted to the oxidative stability test in the Rancimat. A test that indicates the time of the oxidation in the Exploratory Differential Calorimetry (DSC) equipment. It was analyzed the effects in the temperature and the addition of the ethanol cosolvent in the extract yield. The best tenses of induction obtained were for the additive biodiesel with some extracts obtained by the conventional method, both with the ethyl acetate solvent, which took 11,13 hours for the extract obtained in the grease and oils extractor (ExtAcet) and 11,01 hours for the extract obtained in the Soxhlet (SoxAcet). It was checked that these values are higher than the other ones which were found for the additive biodiesel with the synthetic antioxidants BHA (6,91h) and BHT (7,86). Among the extracts obtained by the supercritical extraction, it was highlighted the condition of 35 °C with 5 mL of ethanol (8,01 h) and 55 °C with 5 mL of ethanol (7,77 h).Except the supercritical extract in the temperature of 35 oC without the addition of ethanol, all the extracts presented a time of induction higher than the obtained in the control (4,38 h), however only threeextracts that were added to the biodiesel showed a higher value which is demanded in the Resolution n45/2014 and it predicts oxidative stability of 8h for the test in Rancimat. For the DSC test, the samples that presented a higher time of oxidation were for the ExtAcet (31,42 min) and the supercritical extraction in the condition of 35 °C with 5mL of ethanol (31,25 min). The biodiesel oxidative stability was in the most part higher when it was added to thepomegranate peel in comparison to the pure biodiesel showing efficiency in its utilization as a natural antioxidant.